METODE TAHFIDZ ALQURAN : SEBUAH PENGANTAR - Isramin, Tamrin Talebe, (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2019)
Tahfidz Alquran or memorization of the Koran is the oldest tradition in efforts to preserve the Koran. Along with the history of Islam development, various efforts were made to preserve the tradition. The goal of become a hafidz is to achieve the salvation of his religion through the preservation of the scriptures. Various methods applied as an effort to memorize the Koran. Various methods to memorize Koran including Talqin method and Tikrar method, listening to recordings, movements and gesture methods, method of reading verses to be memorized, memorization method by recording the voice of teachers and children, method of listening to recordings of reading verses of the Qur'an from the teacher and their peers, the Sima'i / Tasmi method, the Muraja'ah method, the Jama' method or the Kitabah method.